Holocene thinning history of David Glacier, Antarctica - James Stutz II (8512248) (2020)
The Antarctic Ice Sheet is a significant component of the Earth System, modulating Earth‘s sea level and climate. Present day and projected ice mass losses from Antarctica are of paramount concern to human populations in low-lying communities around the world. Ocean freshening from future ice discharge events also has the potential to destabilise global climate patterns. Over 40 years of satellite observations have tracked changes in ice mass, extent and thickness in Antarctica. However, ice sheets respond on timescales that range from annual to millennial, and a geologic perspective is needed to fully understand ice sheet response on timescales longer than a few decades. This research seeks to provide an improved understanding of Antarcticas future by constraining its past. I focus on one of the largest outlet glaciers in Antarctica, the David Glacier/Drygalski Ice Tongue system which drains the East Antarctic Ice Sheet, dissects the Transantarctic Mountains and discharges into the Ross Sea. I seek to answer two questions; (1) what is the timing and nature of David Glacier thinning since the Last Glacial Maximum approximately 20,000 years ago, and (2) what physical processes were responsible for the observed thinning? I answer these questions by mapping the terrestrial and marine geomorphology along the former margins and seaward extension of David Glacier, and by using surface exposure dating of bedrock and glacial erratics to constrain the timing of glacier thinning. I then use a numerical flowline model to identify the processes that drove glacier thinning and retreat. Surface exposure ages from bedrock and glacial erratics at field sites both upstream and downstream of the modern grounding line reveal that David Glacier thinned for two millennia during the mid-Holocene. Near the coast, this thinning occurred at ∼6.5 kya at a rapid rate of up to 2 m/yr. Upstream from the grounding line, the thinning was more gradual but occurred simultaneously with thinning downstream. The timing of glacial thinning at David Glacier correlates with thinning events at other glaciers in the region and is consistent with offshore marine geological records. To identify the mechanisms responsible for the observed thinning of David Glacier, I conduct numerical model sensitivity experiments along a 1,600 km flowline, extending from the ice sheet interior to the continental shelf edge in the western Ross Sea. Offshore, the glacier flowline follows the Drygalski Trough, where it crosses numerous grounding zone wedges of various sizes. The flowline and prescribed ice shelf width is guided by the orientation and distribution of mega-scale glacial lineations as well as overall sea floor bathymetry. I explore the response of a stable, expanded David Glacier to the effects of increasing sub-ice shelf melt rates, and decreasing lateral buttressing which may have occurred as grounded ice in the Ross Sea migrated southward of the David Glacier. These forcings were also combined to explore potential feedbacks associated with Marine Ice Sheet Instability. This modelling demonstrates that David Glacier likely underwent rapid thinning over a period of ∼500 years as the grounding line retreated to a prominent sill at the mouth of David Fjord. After a period of ∼ 5 ka of stability, a second period of grounding line retreat in the model leads to the glacier reaching its modern configuration. This simulated two-phase grounding line retreat compares well with onshore geologically constrained thinning events at two sites (Mt. Kring and Hughes Bluff), both in terms of timing and rates of past glacier thinning. This retreat pattern can be forced by either increased ice shelf melting or reduced buttressing, but when combined, lower melt rates and less lateral buttressing is required to match onshore geologic constraints. Together, the findings in this thesis provide new data to constrain the past behaviour of a significant portion of the East Antarctic Ice Sheet and critical insights into the mechanisms that control ice sheet thinning and retreat. Incorporation of these constraints and improved understanding of the underlying mechanisms driving glacier thinning and grounding line retreat will ultimately improve continental scale ice sheet models which are used to project the future behaviour of the Antarctic Ice Sheet and its influence on global sea level.